P261 Asking about bowel control problems in IBD: Results of face-to-face screening vs. self-reporting. (16th January 2018) - Norton, C; Hart, A; Duncan, J; Emmanuel, A; Knowles, C; Kerry, S; Lanz, D; Berdunov, V; Madurasinghe, V; Terry, H; Verjee, A; Dibley, L
Abstract: Background: Patients with IBD have difficulty revealing concerns about bowel control problems to clinicians, 1 who do not actively ask about this symptom 2 despite clinical guidelines recommending active-case finding in high-risk populations. 3 With no available evidence to advise clinicians on how to ask, we aimed to determine the results of face-to-face or self-reported screening to identify faecal incontinence (FI) in IBD patients. We also asked about patients' desire for interventions to improve continence. FI was defined in this study as: 'ever having accidental passing of stool, faeces, poo into your underclothes, that you are either unaware of at the time, or unable to control'. Methods: This cross-sectional survey used a study-specific questionnaire to screen participants at either face-to-face interview (by clinician / researcher) or anonymously (participant self-completed). Eligibility criteria: 18 to 80 years of age, confirmed diagnosis of IBD, no current fistula, no stoma, any level of disease activity. Disease activity was measured using the Harvey Bradshaw Index or the Simple Clinical Colitis Activity Index. Results: Of 1336 participants, 48% were male; mean age 43 years (range 18–80); 55% had Crohn's disease (CD), 41% ulcerative colitis (UC), 4% IBD unclassified. FI (occurring ever) was reported by 63% of 772 screened face-to-face and 56% of 564 self-report participants ( p = 0.012). A total of 38.7% of all respondents expressed interest in an intervention for FI. Patients with CD were more likely to report FI than those with UC ( p = <0.05). FI was reported by 49% of participants in remission, and by 59%, 83% and 93% of participants with mild, moderate and severe relapse of IBD respectively ( p = <0.001). Conclusions: Bowel control problems are very common in patients with IBD (including in remission) and these symptoms can be identified by face-to-face interview and postal screening. Interest in interventions for FI is expressed by 38.7% of patients with IBD. References: 1. Dibley L, Norton C. Experience of fecal incontinence in people with inflammatory bowel disease: self-reported experiences among a community sample. Inflamm Bowel Dis 2013;19:1450–62. 2. Dibley L, Norton C. Help-seeking for fecal incontinence among people with inflammatory bowel disease. J Wound Ostomy Continence Nursing 2013;40:631–8. 3. National Institute for Clinical Excellence. Management of faecal incontinence in adults, NICE, London, Report No: CG 49. 2007.